Pengaruh Keterbatasan Fasilitas Belajar terhadap Academic Persistence pada Mahasiswa ditinjau dari Dukungan Sosial Orangtua - Maria Goreti Imut; Andriani Paulin Nalle; I Putu Agus Apriliana (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2025)
Persistence is a trait that all individuals who want to succeed must possess, refusing to give up in pursuit of their goals despite difficulties. This study aims to determine: (1) the impact of limited learning facilities on academic persistence in terms of parental social support; and (2) investigate the differences in limited learning facilities and academic persistence in terms of parental social support. This study employs a quantitative, descriptive research design. The sample comprised 72 college students. Data collection used an independent instrument based on a theoretical framework of variables, with Likert-scale responses. Data analysis included simple linear regression and independent t-tests. This study finds that the first hypothesis is confirmed: that limited learning facilities have an insignificant influence on the academic persistence of students with high parental social support. For the second hypothesis, the data show that limited learning facilities do not influence academic persistence among students with low parental social support. In the third hypothesis, there are no significant differences in limited learning facilities and academic persistence between students with high and low parental social support. Based on the findings, it can be concluded that limited learning facilities have little impact on academic persistence among college students, regardless of parental social support, and that there are no differences in academic persistence between students with and without limited learning facilities when parental social support is taken into account.